Chapter 12 The usefulness of violent ends apocalyptic imaginaries in the reconstruction of society - van den Heever, Gerhard (Taylor & Francis, 2018)
Throughout 2015 and 2016 there have been constant violent protests, destruction of university property, and clashes between protesters and police and security personnel on various campuses. An apocalyptic worldview is essentially a violent worldview. In the eschatological lore that animates ISIS ideologically, the city of Dabiq in northern Syria near the Turkish border is the site of the end-time apocalyptic war. In the vision of the author of the Dabiq article, immersion in Western society is to be a hypocrite or an about-to-be apostate. The changes in social constitution of Spanish society also brought with them increasing clamour for a political voice. As the Republican government set about its programme of re-engineering Spanish society, to a large extent the Catholic Church became the central focus of the cultural wars escalating in the country. Two political forces played a central role in the unfolding of the civil war: the army and the Catholic Church.